Lélia Gonzalez and Sueli Carneiro, two black roses sowing spring: subsidies for understanding the bonds between capitalism, patriarchy and racism - Gonçalves, Renata; Lourenço, Ana Paula Pires (Argumentum, 2023)
The article addresses the contribution of two black Brazilian intellectuals: Lélia Gonzalez and Sueli Carneiro. Two fundamental black roses in the construction of the black movement in the 1970s and in feminist discussions guided by black women. Many concepts presented today as a novelty were developed by these scholars and activists, who provide us with theoretical-political elements to understand and overcome the intrinsic and current relationship between capitalism, patriarchy and racism.